Electronic transport properties of metal–centrosymmetric zigzag carbon nanotube heterojunction devices with different lengths. (14th April 2015) - Ren, Yun; Hu, Kuang-Sheng; Peng, Xiao-Fang; Bai, Wen-Qi; Peng, Li-Hua
Abstract: From the first-principles calculation, we investigate the electronic transport properties of centrosymmetric carbon nanotube heterojunction with different lengths coupled with between two identical Al(100) electrodes. The results show that the conductance can be modulated with the length of central regular carbon nanotube. The current ratios of different heterojunctions decrease exponentially with the external bias voltage, which provides us a new idea of combination functional element of the next generation of computers. A detailed analysis is proposed.